KINERJA KARYAWAN PT. KREASI PAPAN DIPENGARUHI OLEH BEBAN KERJA MELALUI STRES KERJA - Imam Akbar; Arief Rachmawan Assegaf (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research aims to analyze the performance employees of PT. Kreasi Papan is influenced by workload through work stress. The method used in this research is a quantitative approach. The sampling technique uses a census. The analysis method uses path analysis techniques. The results of the research show that: 1) Work load directly has no effect on employee performance 2) Work stress has no direct effect on employee performance 3) Work load directly has an effect on work stress. 4) Work stress is not an intervening variable between workload and employee performance PT. Kreasi Papan.